Surface studies of radiation grafted sulfonic acid membranes: XPS and SEM analysis - Nasef, Mohamed Mahmoud; Saidi, Hamdani (Elsevier B.V., 2006)
PTFE-g-polystyrene sulfonic acid membranes prepared by radiation-induced graft copolymerization of styrene onto poly(tetrafluoroethylene) (PTFE) films followed by sulfonation reactions were investigated with respect to their morphology and surface chemical properties. The chemical composition of the membranes surfaces was monitored at various degrees of grafting using X-ray photoelectron spectroscopy (XPS). Considerable differences in the concentration of the chemical components of the surfaces were observed despite the predominance of all membranes surfaces by a hydrocarbon fraction originated from the incorporated sulfonated polystyrene grafts. The distribution of the sulfonated polystyrene grafts in membranes having various degrees of grafting was investigated by scanning electron microscopy (SEM). The membranes achieved a homogenous distribution at degrees of grafting of 24% and above. The results of this work suggest that the membranes have a chemically sensitive surfaces and this is most likely to have an impact on their interfacial properties and chemical stability